Comparison Of Percutaneous Nephrolithotomy By The Use Of Pneumatic Lithotripsy Alone Or In Conjunction With Ultrasonic Lithotripsy (Journal of Pharmaceutical Negative Results, 2023)
Background:Percutaneous nephrolithotomy (PCNL) refers to aninvasive process for removinglarge-size stones from the kidney. Pneumatic lithotripsy on the other hand is also an effective procedure in spite of the composition of stones. Lithotripsy through ultrasound helps in aspiring small particles of debris during the procedure of lithotripsy.Objective:This study will investigate the comparative analysis of the percutaneous nephrolithotomy procedure through pneumatic lithotripsy alone or in combination with the ultrasonic lithotripsy approach.Study design: A retrospective case-control studyPlace and Duration: This study was done at Dr Ziauddin Hospital Karachi from October 2021 to October 2022Methodology:A total of 128 participants were recruited for the study and divided into two groups with 69 participants each. Both the groups had undergone neumatic lithotripsy either alone through percutaneous nephrolithotomy or in combination with ultrasonic lithotripsy. Data has been compared for the variables of the location, size, composition, the average range of treatments, time of operation, loss of blood, hospital stay, chances of device failure and rates of free stones.Results:The study has depicted no difference in the variables at the baseline in terms of size, composition and location of the stone, number of treatment sessions provided and the number of stones found within the region. Results of the study show that the treatment provided through the combined approach of neumatic along with ultrasonic lithotripsy has a lower stay within the hospital with a statistically significant p-value of 0.002 and lower time for operation with a p-value of < 0.005. These patients were also observed to have a low loss of blood with a p-value of 0.005. Some patients however required transfusions without any significant complications associated with it.Conclusion: The study concluded that the combined approach has more beneficial effects as compared to a single approach with a lesser stay in the hospital, time of operation and decrease the loss of blood.